Meningkatkan Kepercayaan Diri Pada Anak Melalui Platform Youtobe - Dinda Ayu Lestari; Erni Asbi Asneli (Yayasan Literasi Sains Indonesia, 2022)
Self-confidence is one of the most important aspects of a person's personality. A person's self-confidence is a matter of someone being able to overcome a problem with the best situation and can provide something pleasant for others. Self-confidence as a very valuable attribute in oneself in social life, without self-confidence will cause many things to a person. This is because with self-confidence, a person is able to actualize all his potential. Self-confidence is important for every individual to have. Confidence is needed by both a child and a parent, both individually and in groups. Individuals who are confident will view weaknesses as natural for every individual, because confident individuals will turn their weaknesses into motivation to develop their strengths and will not allow their weaknesses to become an obstacle in actualizing their strengths. Children who are confident will be able to accept themselves, ready to accept challenges in the sense of wanting to try something new even though they are aware that the possibility that a person has and tends to succeed in doing what he wants. Meanwhile, children who lack self-confidence will be pessimistic in facing challenges, afraid and hesitant to express ideas, indecisive in choosing and often compare themselves with others. Because personality development, mental and intellectual attitudes are formed from an early age and need a gradual process, children's self-confidence needs to be built from an early age.